Memperkenalkan Ruang Publik Peninggalan Kota Lama Kendari di Kalangan Mahasiswa Baru - Laxmi Laxmi; La Ode Aris; Zainal Zainal; Erens E Koodoh (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2021)
This service was carried out with the aim of introducing the Old City's public spaces to new students. This service was carried out in Kendari City with the objects being public spaces in the old city. This service uses group discussion techniques with review and reflection methods on field findings. Apart from that, active and critical joint discussions were also held. Based on the results of this service, it can be seen that the old city has very high historical value and the old city is one of the most important factors in marking the growth and development of the city of Kendari as a port city, trading city and government city. The many public spaces that are part of the history of the city of Kendari to date can attract the attention of students to find out or study the history of the public spaces of the people around the old city of Kendari.